2018
DOI: 10.1159/000493968
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of LncRNA H19/miR-194-5p Axis on the Epithelial-Mesenchymal Transition of Colorectal Adenocarcinoma

Abstract: Background/Aims: Since the combined actions of lncRNAs and miRNAs have been considered to be involved in the occurrence and development of various neoplasms, the main purpose of this study was to discover whether and how lncRNA H19 and miR-194 influenced the epithelial-mesenchymal transition (EMT) process of colorectal adenocarcinoma (CRA). Methods: Totally 214 pairs of CRA and adjacent normal tissues were collected, and 5 human CRA cell lines (i.e. HCT116, HT-29, RKO SW280 and Lovo) were purchased. Quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…With the deepening of research, a wide range of cellular processes, such as alternative splicing control and translation, chemical RNA modification, pre-RNA processing and host mRNA stabilisation, have been demonstrated to be related to the dysregulation of lncRNAs [30,31]. Additionally, the interaction network of mRNAs and lncRNAs plays vital roles in the occurrence and recurrence of diverse cancers, and the regulatory mechanism may be linked to the competition in binding miRNA targets [32,33]. SNHG6, as a novel cancer-related lncRNA, is located at chromosome 8q13 and has an evident connection with the structural integrity of the translation initiation complex and ribosomes, and it has become a new frontier of research [34].…”
Section: Discussionmentioning
confidence: 99%
“…With the deepening of research, a wide range of cellular processes, such as alternative splicing control and translation, chemical RNA modification, pre-RNA processing and host mRNA stabilisation, have been demonstrated to be related to the dysregulation of lncRNAs [30,31]. Additionally, the interaction network of mRNAs and lncRNAs plays vital roles in the occurrence and recurrence of diverse cancers, and the regulatory mechanism may be linked to the competition in binding miRNA targets [32,33]. SNHG6, as a novel cancer-related lncRNA, is located at chromosome 8q13 and has an evident connection with the structural integrity of the translation initiation complex and ribosomes, and it has become a new frontier of research [34].…”
Section: Discussionmentioning
confidence: 99%
“…H19 located on human chromosome 11p15.5. Studies have found that H19 overexpressed in various malignancies, which indicated that H19 overexpression could upregulate the proliferation of tumor cells and promote tumor cell migration and invasion [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of lncRNAs has been welldocumented in different sorts of cancers [8]. Dysregulation of lncRNA HOTAIR, H19, MALAT1, SNHG7, GAS8-AS, and NEAT1 were extensively well-studied and have been demonstrated to contribute in tumorigenesis and poor prognosis [5,[8][9][10][11][12]. A mounting of investigations have shown that lncRNAs exert their function through competing for endogenous RNA (ceRNA) crosstalk [13].…”
Section: Introductionmentioning
confidence: 99%